2008
DOI: 10.1089/acm.2007.0606
|View full text |Cite
|
Sign up to set email alerts
|

Visualized Regional Hypodermic Migration Channels of Interstitial Fluid in Human Beings: Are These Ancient Meridians?

Abstract: We imaged 6 regional migration channels originating from 6 acupoints on 6 yin meridians of hand and foot by injecting a minimal amount of tracer into acupoints directly in humans. The responses of the subcutaneous specific channels to acupuncture needling are different from those of lymphatic or blood vessels and coincide partially with the characteristics of acupuncture therapeutics, suggesting the existence of meridian-like channels in humans. These findings may contribute to further research on the specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 13 publications
4
41
0
Order By: Relevance
“…Taiyuan (LU9) of the Lung Meridian, which is located at the wrist crease on the radial side of the radial artery, was selected for the fluorescence imaging experiments. As described previously [5], a small amount of contrast agent was injected into subcutaneous loose connective tissues at a depth of 1-2 mm prior to image acquisition. Each subject consented to the administration of acupuncture at one or two acupuncture points on sequential days.…”
Section: Selection Of Acupuncture Pointsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taiyuan (LU9) of the Lung Meridian, which is located at the wrist crease on the radial side of the radial artery, was selected for the fluorescence imaging experiments. As described previously [5], a small amount of contrast agent was injected into subcutaneous loose connective tissues at a depth of 1-2 mm prior to image acquisition. Each subject consented to the administration of acupuncture at one or two acupuncture points on sequential days.…”
Section: Selection Of Acupuncture Pointsmentioning
confidence: 99%
“…However, in studies investigating ancient meridian pathways by injecting various low molecular weight tracers within specific regions of the skin (generally acupuncture points), non-vascular drainage pathways can be visualised in animals as well as in humans [1][2][3][4][5]. In animals, these pathways, which conform to the perivenous loose connective tissues (PLCTs) along venous trees (including the venous adventitia), are capable of draining free fluid [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the long interstitial tissue channels observed by Casley-Smith with an electron microscope are in fact the interstitial fluid flow [4]. The tracer (Gd-DTPA) injected into acupoints travels with interstitial fluid flow; therefore, their observance of flow different from blood and lymph flow may reflect the interstitial fluid flow [5]. If we change the diffusion coefficient from the secretion protein to the tracer (500 μm 2 /s) [24], there will be directional flow of the tracer similar to that in Fig.…”
Section: Explanation Of Some Experimental Observations By Directionalmentioning
confidence: 99%
“…For example, CasleySmith et al [4] examined the marked interstitium with an electron microscope and found interstitial tissue channels with the width of 50-100 nm and the maximum length of several centimeters in rats and rabbits. Li et al [5] visualized regional hypodermic migration channels of interstitial fluid in humans with magnetic resonance imaging (MRI). These channels were different from those of lymphatic or blood vessels and partially coincided with the characteristics of meridian.…”
Section: Introductionmentioning
confidence: 99%